Another GO at the experiment. - Howard, Leslie W.; Garman, Karen A.; McCann, Rose-Elaine (Public Health Reports)
A pilot evaluation study was carried out to assess legislative efforts in California to allow unlicensed international medical graduates to become physician assistants (PAs). Such efforts have been made in a number of states, but so far they have failed. The medical knowledge of a group of unlicensed international medical graduates was assessed, and their results were compared with a control group consisting of recent graduates from a PA training program. The medical knowledge and clinical skills of all of the unlicensed international medical graduates tested were below standard. In addition, in tests with standardized patients, these graduates failed to make critical diagnoses. Before they can be incorporated into the U.S. health care system as PAs, unlicensed international medical graduates will need to undergo additional training.